The Gingiva from the Tissue Surrounding the Bone to the Tissue Regenerating the Bone: A Systematic Review of the Osteogenic Capacity of Gingival Mesenchymal Stem Cells in Preclinical Studies - Gamilah Al-Qadhi; Iman Aboushady; Niyaz Al-Sharabi (Stem Cells International)
The current review aims to systematically assess the osteogenic capacity of gingiva-derived mesenchymal stem cells (GMSCs) in preclinical studies. A comprehensive electronic search of PubMed, Embase, Web of Science, and Scopus databases, as well as a manual search of relevant references, was performed in June 2020 without date or language restrictions. Eligibility criteria were the following: studies that compared mesenchymal stem cells (MSCs) derived from the gingiva with other MSC sources (in vitro or in vivo) or cell-free scaffold (in vivo) and studies that reported at least one of the following outcomes: osteogenic potential and new bone formation for in vitro and in vivo, respectively. Moreover, the assessment of included studies was conducted using appropriate guidelines. From 646 initial retrieved studies, 35 full-text articles were subjected to further screening and 26 studies were selected (20 in vitro studies and 6 in vivo studies). GMSCs showed great proliferation capacity and expressed recognized mesenchymal stem cell markers, particularly CD90. In vitro, MSC sources including GMSCs were capable of undergoing osteogenic differentiation with less ability in GMSCs, while most in vivo studies confirmed the capacity of GMSCs to regenerate bony defects. Concerning the assessment of methodological quality, in vitro studies met the relevant guideline except in five areas: the sample size calculation, randomization, allocation concealment, implementation, and blinding, and in vivo publications had probably low risk of bias in most domains except in three areas: allocation concealment, attrition, and blinding items.